1997
DOI: 10.1002/(sici)1097-0215(19970620)74:3<270::aid-ijc6>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a breast-cancer-associated protein (pS2) in human neuro-endocrine tumours

Abstract: pS2 protein expression has been demonstrated in a range of malignant tissues in an oestrogen-independent pathway. Recently, it has been demonstrated that pS2, in prostate cancer, is closely associated with neuro-endocrine differentiation. In the present study, we have analyzed, by immunohistochemistry along with microwave antigen retrieval, the expression of pS2 protein in a retrospective series of 236 human primary neuro-endocrine tumours and attempted to correlate this with the clinicopathologic features of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Maisakowski et al first described the pS2 gene in the MCF-7 human breast cancer cell line [6]. The pS2 is a cysteine rich secretory protein, containing 84 amino acids and a molecular weight of 6.45 k-Da.…”
Section: Introductionmentioning
confidence: 99%
“…Maisakowski et al first described the pS2 gene in the MCF-7 human breast cancer cell line [6]. The pS2 is a cysteine rich secretory protein, containing 84 amino acids and a molecular weight of 6.45 k-Da.…”
Section: Introductionmentioning
confidence: 99%
“…However, Bonkhoff et al 16 showed that TFF1, in prostate cancer, is closely associated with premalignant changes and neuroendocrine differentiation and we have recently showed TFF1 expression in some neuroendocrine tumours. 17 In the present study, we report the expression of the TFF1 protein in human sporadic and familial MTCs.…”
Section: Introductionmentioning
confidence: 85%
“…17 Briefly, 4 m paraffin sections were dewaxed and subjected to microwave antigen retrieval by immersion in citrate buffer, pH 6·0. Endogenous peroxidase was blocked with 3 per cent hydrogen peroxide for 15 min and sections were treated with 20 per cent normal rabbit serum for 20 min.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Slides were deparaffinized as described above. Antigen retrieval was done by the microwave antigen retrieval method [8]. Blocking was done by incubating 200 mL of 10% sheep serum in PBS at 37ЊC (1 h) followed by 2 washes in PBS.…”
Section: Methodsmentioning
confidence: 99%